Glucose transporter 1 in health and disease - Pragallapati, Sindhuri (J Oral Maxillofac Pathol, 2019)
Glucose, a major source of energy for all cells, is transported into cells with the help of glucose transporters (GLUTs). These transporters are of two types, namely sodium-dependent GLUTs and facilitative GLUTs. These transporters are present in a tissue-specific pattern and have substrate specificity. Among these transporters, GLUT1 (facilitative GLUT) is present ubiquitously on all tissues of the body and helps in the basal uptake of glucose. GLUT1 is known to have many physiological functions in the body from the time of implantation of an embryo and is also seen associated with pathologies, including cancers. This review mainly focuses on GLUT1 in physiological and pathological conditions and the recent advances related to its role in cancer development and applications in cancer therapeutics.